Factors Influencing the Implementation of Electronic Medical Records (EMR) Using the Human, Organization, and Technology Fit (HOT-Fit) Approach: EMR Implementation and HOT-Fit Factors - Amrullah, Seno Arif; Suprapto, Sentot Imam; Indasah (CV. Paperhome Indonesia, 2025)
Background: Hospitals as health care facilities have an obligation to patients to provide fast and precise services using complete facilities, one of the efforts of health services in improving service quality is to utilize health information technology. Major challenges are still faced by medical personnel as the main users of the system, especially in terms of ease of access, data interoperability, and time efficiency in medical records. The purpose of the study was to analyze the factors that influence the implementation of Electronic Medical Records (EMR) with the Human Organization Technology (HOT) FIT approach at Ahmad Dahlan Kediri Hospital. Method : Observational research design with a cross-sectional approach. The population of all health workers at Ahmad Dahlan Kediri Hospital is 382. The sample taken in this study was 192 respondents through the Krejcie and Morgan formula with purposive sampling technique. Independent variables are human resource aspects, organizational aspects and technological aspects. The dependent variable is the application of EMR. The research instrument used a questionnaire taken from previous research. The analysis used was univariate analysis, bivariate analysis and multivariate with linear regression using SPSS 23. Results: The linear regression test conducted shows that there is a relationship between family support (p=0.000) and government support (p=0.000) on the quality of life of the elderly, the most influential variable is family support with a significance level of p=0.000 and B=0.246. Then, the second analysis shows that there is a relationship between family support (p=0.000) and government support (p=0.018) on the health status of the elderly, the most influential variable is family support with a significance level of p=0.000 and B=0.447. Conclusion: In the early stages of using EMR, many medical personnel experience difficulties in adapting to the new system. Some of the obstacles that often occur are lack of adequate training, resistance to change, and limited infrastructure that supports the implementation of EMR. Therefore, a comprehensive strategy is needed to improve the skills of medical personnel in using the system, including continuous training and socialization.